Production Planning of The Instant Tea With Peppermint Flavor for Home Industry Scale - Sukardi, Sukardi; Pulungan, M. H.; Kurniawan, K. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2009)
The aim of this research was to know the right sugar and peppermint oil concentration and their effect to physic-chemistry value of instant tea with peppermint flavor, and to get the description of instant tea with peppermint oil flavor production planning in home industy scale by financial aspect. Research methode difind as: deskriptive research, Â experimental research, consumer preference, determination of the best products and production planning and feasibility by financial analysis consisted of break event point and payback period. Experimental research with Randomized Block Design by two factors. First factors was sugar concentration (150%, 200% and 250%) and second factors was peppermint oil concentration (0.1%, 0.2% and 0.3%).Â The best treatment of instant tea with peppermint oil flavor by using 250% sugar concentration and 0.3% peppermint oil concentration with preference value: color 4.2 (like), taste 4.2 (like), smell 3.8 (neutral) and clearness 4.2 (like) with physic-chemistry values: 68.74% yield, 0.23% tannin concentration, 4.02% moisture contents and 99.92% solubility. Production planning with 2.62 kg/day capacity of instant tea with peppermint oil flavor (131 sachet/day or 26 box/day), workers requirement is two man with work based time process needed. Base Production Price is Rp. 576.62 with 50% mark-up we get selling price Rp. 864.93/sachet. Break Event Point calculation at 7,767.63 sachet was selling equal to Rp 6,718,477.45. Payback Period was one years, eight month and tree days. According to financial aspect calculation, home industry founding of instant tea with peppermint flavor is feasible.Keywords : instant tea, peppermint